La estructura del gasto operativo de la Cooperativa de Ahorro y Crédito Cacha ltda. y su incidencia en la rentabilidad, cantón Riobamba, período 2013-2014. - Yumbo Pilamunga, María Zoila (2016)
The main reason for the realization of this work, detailed in the structure of operating expenses held by the institution for their activities, and the items that are within the same inflated considerably the monetary value that disburses the entity to meet their business needs A decline in profits in the credit Cooperative Cacha Ltda reflected., because expenses that are not part of the normal rotation of the institution but are included in the items for operating expenses, are to which they can be called sunk costs or hidden marketing expenses, representing the same incorrect administrative decisions and inadequate control of them. Effective institutional control for the development of a model Activity Based Costing (Activity Based Costing) "ABC" is proposed; the costing system "ABC" allows a financial institution, focusing proper management to analyze the cost structure of its products and services, enabling you to locate limitations and possible existing threats, in order to develop strategies to mitigate the risks to which the institution is exposed, avoiding problems that threaten the sustainability of it. This management information system identifies the direct costs are not assignable in products and services but in the activities developed to produce such products. For the development of this model should take into account the previous analysis of performance documents within the institution, involvement causing components required undergo changes and how they affect the objectives of the institution and in this case operational costs directly affect the economic performance of the credit cooperative Cacha Ltda.